Human Immunodeficiency Virus Integration Efficiency and Site Selection in Quiescent CD4(+) T Cells - Vatakis, Dimitrios N. (American Society for Microbiology (ASM), 2009)
Until very recently, quiescent CD4(+) T cells were thought to be resistant to human immunodeficiency virus (HIV) infection. Subsequent studies, attempting to fully elucidate the mechanisms of resistance, showed that quiescent cells could become infected by HIV at low efficiency and form a latently infected population. In this study, we set out to identify the sites of viral integration and to assess the efficiency of the overall integration process in quiescent cells. Based on our results, HIV integration in quiescent CD4(+) T cells occurs in sites similar to those of their prestimulated counterparts. While site selections are similar, the integration process in quiescent cells is plagued by the formation of high levels of incorrectly processed viral ends and abortive two-long-terminal-repeat circles.